2014
DOI: 10.1039/c4ob01268b
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-free MCR for linking quinoxaline framework with a benzimidazole nucleus: a new strategy for the identification of novel hybrid molecules as potential inducers of apoptosis

Abstract: We report a true MCR involving the reaction of N-(prop-2-ynyl)quinoxalin-2-amine derivatives with 2-iodoanilines and tosyl azide in the presence of 10 mol% of CuI and Et3N in DMSO to afford the pre-designed hybrid molecules containing quinoxaline framework linked with a benzimidazole nucleus. The MCR proceeds in the absence of any ligand and/or lateral addition of the catalyst/base affording products within 30 min in good yields, some of which showed encouraging apoptosis inducing properties in zebrafish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
(1 reference statement)
0
12
0
Order By: Relevance
“…The anticancer activity studies revealed that these compounds induced signicant apoptosis in zebrash embryos. 29 In another study, green chemistry was applied to link the three pharmacophoric groups (quinoline, triazole, and dihydroquinoline) to form a novel series of hybrid molecules. The process involved one-pot sequential azidation and coppercatalyzed azide-alkyne cycloaddition (CuAAC) in water under mild conditions.…”
Section: Azole-based Hybridsmentioning
confidence: 99%
“…The anticancer activity studies revealed that these compounds induced signicant apoptosis in zebrash embryos. 29 In another study, green chemistry was applied to link the three pharmacophoric groups (quinoline, triazole, and dihydroquinoline) to form a novel series of hybrid molecules. The process involved one-pot sequential azidation and coppercatalyzed azide-alkyne cycloaddition (CuAAC) in water under mild conditions.…”
Section: Azole-based Hybridsmentioning
confidence: 99%
“…The multicomponent strategy has provided an easy access to the synthesis of complex bioactive molecules with multiple point diversity incorporating up to eight components in one-pot [8]. The pharmaceutical industry has witnessed a considerable surge in drug synthesis via multicomponent strategies [9][10][11], including the synthesis of atorvastatin, a potent HMG-CoA reductase inhibitor. Dömling and co-workers efficiently demonstrated an Ugi-based MCR approach towards the synthesis of atorvastatin in four steps ruling out the lengthy seven step protocol, and paving a rapid entry to the drug discovery market [12].…”
Section: Introductionmentioning
confidence: 99%
“…These drugs are known to hinder the breakage/reunion reaction of topoisomerase I, in which the enzyme is reversibly trapped in a state where the DNA is cleave 6 . Furthermore, benzimidazole is known to be a versatile scaffold that possess potential anticancer, antitumor and antiproliferative activities [21][22][23][24][25][26][27] . Similarly, oxadiazole has engrossed significant attention of medicinal chemists owing to their wide range of useful pharmacological actions particularly cytotoxic activities against DNA topoisomerase I [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%